2014
DOI: 10.1159/000363187
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Dry Age-Related Macular Degeneration

Abstract: A number of different approaches are under development for treating nonexudative manifestations of age-related macular degeneration (AMD). Some interventions target specific pathways that are believed to play a role in AMD pathogenesis, e.g. oxidative damage, lipofuscin accumulation, chronic inflammation (including complement activation), extracellular matrix changes (e.g. β-amyloid accumulation), impaired choroidal blood flow, and apoptosis. In principle, these therapies can be combined (‘combination therapy'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…2,3,6 The management of patients with dry AMD remains a significant challenge because dry AMD is managed using non-specific therapies. 11,12 Unfortunately, these therapeutic modalities do not address the underlying primary mechanisms of disease development. Because of the lack of effective therapeutic options available to the patients with dry AMD, there is a pressing need to develop additional treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,6 The management of patients with dry AMD remains a significant challenge because dry AMD is managed using non-specific therapies. 11,12 Unfortunately, these therapeutic modalities do not address the underlying primary mechanisms of disease development. Because of the lack of effective therapeutic options available to the patients with dry AMD, there is a pressing need to develop additional treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, no effective treatment option is currently available. 11,12 Novel therapeutic targets for dry AMD need to be discovered.…”
mentioning
confidence: 99%
“…The median FD plasma level was shown to be approximately 30% higher in AMD patients than in age-matched controls [69]. In view of the central role of FD in the C3 feedback loop and its raised levels in AMD, it has been suggested that it is one of the complement proteins that could be therapeutically targeted in AMD patients [76]. We have recently shown that lutein supplementation was able to markedly decrease the levels of plasma FD and the activation products C3d, C5a and sC5b-9 in patients with early AMD [77,78].…”
Section: Complement Factor Dmentioning
confidence: 99%
“…Once the damage has been done, one would tend to think that the role of complement in further damage could be limited. The fact that clinical trials show that FD blockade still has an effect in late AMD [76] indicates that the damaging effect of complement is ongoing.…”
Section: Amd: a Disease Caused By A Hyperactive Complement Systemmentioning
confidence: 99%
“…As in many other diseases with an inflammatory component, the alternative complement pathway has been implicated in the development of AMD [5]; this mechanism of action is now well known and described [6]. …”
Section: Inhibitors Of Complement Factorsmentioning
confidence: 99%